Facile one-pot synthesis of functional hydrochar catalyst for biomass valorization. (1st May 2022) - Liu, Jianglong; Yang, Luhan; Shuang E; Jin, Caidi; Gong, Chunxiao; Sheng, Kuichuan; Zhang, Ximing
Highlights: Aluminum-oxide nanoparticles loaded on hydrochar with crystalline size less than 0.5 nm. The aerobic calcination contributed the formation of Al-oxide active sites. The glucose isomerization followed the catalytic mechanism of intramolecular 1, 2-hydride shift. Carbon deposition mainly causes catalyst deactivation. Abstract: Corn stover derived hydrochar (HC) doped with aluminum nanoparticles was synthesized through the facile one-pot hydrothermal carbonization for glucose to fructose isomerization. Amorphous aluminum nanoparticles with crystalline size less than 0.5 nm were uniformly loaded on hydrochar. The phase of the Al-oxide nanoparticles was tailored through aerobic/anaerobic calcination. The results showed that the amorphous aluminum nanocrystals with six coordinated Al-oxide structure were formed under oxygen calcination, which facilitated the high catalytic activity and selectivity of glucose isomerization. It was found that catalysts prepared at hydrothermal temperature of 180℃ and further calcinated at 300℃ under aerobic condition (Al/HC180 -300/O) achieved a fructose yield of 42.6% and a selectivity of 83.6% at 180 °C for 5 min. The kinetics, catalytic mechanism, and the deactivation mechanism of the glucose to fructose were further studied using Al/HC180 -300/O catalyst. This study provides a high energy efficiency and low metal loading carbon-based catalysts synthetic approach applicable for biorefinery.